Serão as altas habilidades/superdotação invisíveis? - Cruz, Carly (2014)
The research aimed to analyze the conceptions of high abilities/giftedness under the perspective of the special education teachers who work in the quoted area through their narratives, as well as, the imbrications of these conceptions in the identification of students with evidences of such condition. For the development of the work, we searched via bibliographical review contextualize the theme high abilities/giftedness . The research of qualitative nature was conducted under the contribution of the historical-cultural approach, having the case study as the proposal. These options anchor in our understanding that the high abilities/giftedness are conditions built up via interaction of biological factors with the experiences mediated with the/in the world. We have highlighted the usage of the focal group as a data collection technique to perform this investigation. The subjects involved were the ten Special Education teachers who worked in the specialized educational assistance for high abilities/giftedness , in the resource room, situated in municipalities of Grande Vitória. The discussion of the focal group was analyzed in two moments, namely the narratives produced by the teachers who participated of the first meeting of the focal group and later, with the inclusion of the participants of the first and second meeting of the group. Therefore, there were eight participants in the first meeting and seven in the second one. The analysis of the collected data in two meetings of the focal group was done according to the perspective of Gonzalez Rey‟s Subjectivity Theory (2005). The analysis points out the direct influence of the teachers‟ perceptions concerning their high abilities/giftedness conceptions regarding the specialized educational assistance in the area, as well as in the identification process that was subjectively perceived in the discussions of the focal group. It was perceived that, for the non theoretical consistence concerning the conception of the high abilities/giftedness , the identification of the student with evidences of this condition is confused. The analysis suggests the necessity of a deepening and theoretical consensus about the high abilities/giftedness area, especially, among the teachers of the area, as the main point for the visibility of the theme.